Pengaruh Firm Size, Liquidity, Leverage, CCC dan Inventory Turnover terhadap Profitabilitas Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia - Yandi Suprapto; Nia Enjeliana (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
This study aims to analyze the influence of the management component working capital to profitability that can be measured with ROA and ROE. Components in the form of firm size, liquidity, leverage, cash conversion cycle, and inventory turnover. The research object is a manufacturing company listed on the Indonesia Stock Exchange. This quantitative research takes data from the financial statements for the period 2015 to 2019. The data is tested using the panel data regression method through SPSs 25 and eviews 11. The method used is purposive. sampling, the sample meets the requirements of 144 companies or 720 observational data. The results showed that firm size, liquidity, leverage, cash conversion cycle had a significant effect on ROA but inventory turnover had no significant effect on ROA. Leverage has a significant effect on ROE but firm size, liquidity, cash conversion cycle, inventory turnover has no significant effect on ROE.